2014
DOI: 10.1371/journal.pone.0088490
|View full text |Cite
|
Sign up to set email alerts
|

Association between the XPG Asp1104His and XPF Arg415Gln Polymorphisms and Risk of Cancer: A Meta-Analysis

Abstract: BackgroudThe XPG (xeroderma pigmentosum type G) Asp1104His and XPF (xeroderma pigmentosum type F) Arg415Gln polymorphisms had been implicated in cancer susceptibility. The previous published data on the association between XPG Asp1104His and XPF Arg415Gln polymorphisms and cancer risk remained controversial.Methodology/Principal FindingsTo derive a more precise estimation of the association between the XPG Asp1104His and XPF Arg415Gln polymorphisms and overall cancer risk, we performed a meta-analysis to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 86 publications
(59 reference statements)
0
17
0
Order By: Relevance
“…On the other hand, several mechanisms are involved in the development of Rb such as the disruption of the DNA repair system [25]. The genomic alteration of this system has been associated with other types of cancer such as colorectal cancer (CRC) [26], glioma [27], lung cancer [28,29], head and neck squamous cell carcinoma [30], melanoma [31] and breast cancer [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, several mechanisms are involved in the development of Rb such as the disruption of the DNA repair system [25]. The genomic alteration of this system has been associated with other types of cancer such as colorectal cancer (CRC) [26], glioma [27], lung cancer [28,29], head and neck squamous cell carcinoma [30], melanoma [31] and breast cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that SNPs of the XPG gene are associated with several cancers. The Asp1104Hist polymorphism helped to increase the risk of CRC [25,42]. He et al (2014) reported a significant decrease in the risk of melanoma for the C/C genotype (OR = 0.32; CI of 95% = 0.13-0.75; p < 0.05) [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COOH-terminal domain of the XpG protein contains many alkaline amino acids and changes the alkaline acid amino to an acid (His -Asp), which can significantly alter its ability to interact with other proteins. The results of a meta-analysis indicate that the replacement may be a risk factor for different types of cancer (He et al 2014).…”
Section: Associations Of Studied Snp In Repair Genes With Cytogeneticmentioning
confidence: 99%
“…Studies of DNA adduction/damage, including that produced by tobacco carcinogens and associated repair processes, have identiˆed various metabolic and DNA repair genes with functional polymorphisms (26,(36)(37)(38)(39)(40)(41). A recent meta-analysis showed that representative SNPs in TP53 (tumor protein p53), OGG1 (8-oxoguanine DNA glycosylase), CYP1A1 (cytochrome P450, family 1, subfamily A, polypeptide 1), and EPHX (epoxide hydrolase 1, microsomal (xenobiotic)) were associated with increased lung cancer risk (42)(43)(44)(45)(46) (Table 2).…”
Section: Functional Polymorphisms In Dna Repair and Metabolic Genesmentioning
confidence: 99%